MEMBANGUN PERADABAN DENGAN KONSEP MUTTAQIN DAN IMAMA - Tharaba, M Fahim (J-MPI (Jurnal Manajemen Pendidikan Islam), 2017)
Civilization is built not only in the form of idofact, it needs to be felt in the real form in sociofact, even manifested in artifact. In bringing about an independent civilization, Islam has a very remarkable concept in the form of the concept of muttaqin and imama. This article discusses the competencies exemplified by Rasulullah saw in building civilization through education and the concept of muttaqin and imam in building a generation with civilization